Once upon a time we ate animals : the future of food - Voorst, Roanne van (HarperOne, an imprint of HarperCollinsPublishers, 2021)
"Though increasing numbers of people know that eating meat is detrimental to our own health and the planet's, many still can't be convinced to give up eating meat. But how can we change behavior when common arguments, scientific data, and information aren't working? Acclaimed anthropologist Roanne van Voorst changes the dialogue. In Once Upon a Time We Ate Animals, she shifts the focus from the present looking forward to the future looking back-imagining a world in which most of us no longer use animals for food, clothing, or other items. By shifting the viewpoint, van Voorst offers a clear and compelling vision of what it means to live in a world without meat. A massive shift is already taking place-everything van Voorst covers in this book has already been invented and is being used today by individuals and small organizations worldwide. Hopeful and persuasive, entertaining and informative, Once Upon a Time We Ate Animals offers a tantalizing vision of what is not only possible but perhaps inevitable"--